2021
DOI: 10.3390/nano11102665
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Mediated Synthesis of Zeolitic Imidazolate Framework-8: Effect of Molecular Hydrophobicity, Charge Number and Charge Location

Abstract: Three amphiphilic peptides with varied molecular hydrophobicity, charge number and charge location have been designed as regulators to modulate the crystal growth of zeolitic imidazolate framework-8 (ZIF-8). All three peptides can interact with ZIF-8 to inhibit {100} facet growth and produce truncated cubic crystals. The peptide’s molecular hydrophobicity plays a dominant role in defining the final morphology and size of the ZIF-8 crystals. The peptides with less charge and higher hydrophobicity can promote nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(81 reference statements)
0
4
1
Order By: Relevance
“…The synthesis conditions and time dictate the morphology of the nanoparticles. In our case, spherical nanoparticles were obtained as a result of a less reaction time of 5 min, whereas several other studies have reported rhombic dodecahedral shaped particles involving larger reaction time (12 h or more) 26 , 27 . The hydrodynamic diameter of the particles using DLS measurements was found to be 211.9 nm with a low polydispersity index (PDI) of 0.025, confirming formation of uniform particles (Fig.…”
Section: Resultscontrasting
confidence: 59%
“…The synthesis conditions and time dictate the morphology of the nanoparticles. In our case, spherical nanoparticles were obtained as a result of a less reaction time of 5 min, whereas several other studies have reported rhombic dodecahedral shaped particles involving larger reaction time (12 h or more) 26 , 27 . The hydrodynamic diameter of the particles using DLS measurements was found to be 211.9 nm with a low polydispersity index (PDI) of 0.025, confirming formation of uniform particles (Fig.…”
Section: Resultscontrasting
confidence: 59%
“…Figure S1 shows the evolution of the solution turbidity at 400 nm as a function of the reaction time in each case. Compared with pure ZIF-8, the introduction of amino acids accelerated the nucleation and growth of ZIF-8 Figure a 1 –a 6 shows the TEM morphologies of the ZIF-8 crystals prepared in each case.…”
Section: Resultsmentioning
confidence: 99%
“…With the introduction of amino acids, the size of the ZIF-8 crystal decreased, and the shape changed from rhomboid dodecahedron to cubic. The AA molecules are suggested to be adsorbed on the surface of ZIF-8, acting as a capping agent to inhibit the (1 0 0) facet growth. , Figure b shows the TEM size distribution histogram of AA–ZIF-8. The particle sizes of Ala–ZIF-8, Gly–ZIF-8, Ile–ZIF-8, Leu–ZIF-8, and Val–ZIF-8 are approximately 180 ± 40, 130 ± 30, 250 ± 30, 230 ± 25, and 200 ± 28 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations